Solve the system of equations using substitution.

y = x + 6
y = –2x – 3
LauLUISA
Asked Dec 21, 2012
There are four examples on Khan Academy at the link below:

https://www.khanacademy.org/math/algebra/systems-of-eq-and-ineq/systems-of-eq-overview/v/solving-systems-by-substitution-1
Rob
Answered Dec 21, 2012
x+6=-2x-3
3x=-9
x=-3

easy.
but not sure what the substitution is, cause I don`t learn math in English
boyyyyyy
Answered Apr 29, 2013

TIP: If it's not your answer to this question, please click "Leave a Comment" button under the question to communicate with the question owner.

Categories